The Message Behind the Mural at Lembaga Pembinaan Khusus Anak DKI Jakarta - Refansyah, Edgar Bayu (Universitas Negeri Malang, 2024)
Mural media is one of the methods for children to express their motivation and convey their messages. The purpose of this research is to see how the motivation and also the sociological message conveyed by fostered children in LPKA through media murals. Previous research has a topic about messages conveyed through media murals in public spaces. In previous studies, the weaknesses found are the absence of an explanation of the specific deepening of the message of the mural created by fostered children. This study argues that children in conflict with the law have the right to express their voices through any media. The theoretical approach used in this study is Blumer's Symbolic Interactionism and McClelland's Achievement Motivation Theory. The data collection method used is participant observation and interviews with 15 children who participated in the training and mural painting process at the Lembaga Pembinaan Khusus Anak Kelas 2 Jakarta. The results of the activity are the findings regarding the drive for achievement, the drive to achieve power/power and the drive for affiliation by the fostered children, and the existence of sociological messages that have special meaning from the mural works drawn by fostered children at LPKA Class 2 Jakarta.